Effects of Different Urban-Vegetation Morphology on the Canopy-level Thermal Comfort and the Cooling Benefits of Shade Trees: Case-study in Philadelphia. (March 2021) - Sabrin, Samain; Karimi, Maryam; Nazari, Rouzbeh; Pratt, Joshua; Bryk, Joshua
Highlights: Cooling benefits of street trees were assessed for different urban-morphological scenarios. Mixed-use areas provide highest pedestrian thermal comfort without trees and benefit from tree plantation. Adult shade trees added maximum cooling benefits in residential areas followed by mixed-use areas. Shade trees contributed insignificantly in improving thermal comfort level for the commercial sites Abstract: Urban morphology directly influences heating or cooling rate in street canopies. This paper assessed cooling benefits of street-trees in Philadelphia city, PA considering morphological elements. We assessed summertime thermal comfort for humid subtropical climate (i.e. Philadelphia) by studying human-biometeorological parameters such as Mean-radiant temperature (Tmrt ) and Physically Equivalent Temperature (PET) utilizing Rayman model. This paper will; 1. Quantify impacts of built environment with and without existing vegetation on pedestrian level temperature, 2. Observe impacts of Tmrt, surface temperature (Ts), PET and global radiation at road intersections in five different scenarios where urban canopies are characterized as: a) built environment without vegetation (BE), b) built environment with existing vegetation (BEEV), c) built environment with additional vegetation after 1-year (BEAV-1), d) built environment after 5-years (BEAV-5) and e) built environment after 10-years growth period (BEAV-10). Compared results with the BE scenario suggest that, planting trees in residential and mixed-use sites with higher Sky-view factor (SVF) can improve pedestrian comfort in the long-term by reducing Tmrt, and PET, compared to the commercial sites with lower SVF and Ts . Mixed-use sites were observed to provide highest thermal comfort and further benefit from tree plantation, while commercial sites receive lowest cooling benefit from street trees.